Cryosurgery in a dermatology setup: a hospital based study - Deeptara Pathak Thapa; Anil Kumar Jha; Shristi Shrestha; Smita Joshi (Our Dermatology Online, 2018)
Background: Cryosurgery is the well-aimed and controlled destruction of diseased tissue by application of cold. It has been shown to be effective and efficient in various skin diseases. We studied the indications and outcome of this modality of treatment in our set up. Materials and Method: All patients who were subjected to cryosurgery for different clinical indications were included in the study. Results: There were total of 133 patients. Commonest age group presentation (between 16 to 25 years) constituted about 42%. 52% of patients were students. There were total of 91% who were from Kathmandu remaining 9% were from outside of Kathmandu Valley. Cryosurgery was indicated commonly in warts for 82% patients followed by 12% for keloid & hypertrophic scar, benign conditions in 4% and in premalignant conditions for 2% patients. Number to treatment (or sessions) for indicated disease with resolution of disease was single in 81% patients followed by between 2 to 5 treatment session in 14% and more than 5 treatments was necessary in 5%. Side effects like pain was seen in 64% patients, erythema in 8% and blistering 4%. 24% patients did not have any side effect. Conclusion: Cryotherapy is considered as one of the effective modality of treatment for various skin conditions with various limitations. Further prospective clinical trial with large population group should be carried out.